EFFECT THROUGH E-MAIL MARKETING DECISION TO PURCHASE PRODUCTS AT CHEMICAL AND PAPER RETAIL INDUSTRY IN DEPOK - Mujiyana, Mujiyana (Accounting, 2010)
The purpose of this study was to examine the influence of via e-mail marketing and relationship marketing through e-mail to the purchasing decision. This writing method validity and reliability test, normality test, the classical assumption deviations, correlation matrices and regression test. Results obtained from this study show the relationship between the dimensions of promotional e-mail and e-mails related to the total service purchase decisions happen very strong relationship with a coefficient of 0742 or a percentage of 74.2%. Based on the regression test can also be stated that the dimensions of promotional e-mail address in item 3, item 5 and item 6 directly affects the buying decision. While item 1, item 2 and item 4 does not affect the purchase decision. So the regression equation obtained from the analysis is Y = 1997 0.628X1 0.079X2 0.806X3 0.563X4 1.890X5 1.022X6. Keyword : Promotional, E-mail, Marketing.